Central Administration of Insulin Combined With Resistin Reduces Renal Sympathetic Nerve Activity in Rats Fed a High Fat Diet - Habeeballah, Hamza; Alsuhaymi, Naif; Stebbing, Martin J.; Badoer, Emilio (Frontiers in Physiology, 2019)
Insulin receptors are widely distributed in the central nervous system and their activation by insulin elicits renal sympatho-excitatory effects. Resistin, an adipokine, promotes resistance to the metabolic effects of insulin. Resistin also induces increases in renal sympathetic nerve activity (RSNA) by acting in the brain, but whether it can influence insulin’s actions on RSNA is unknown. In the present study we investigated, in male Sprague-Dawley rats (7-8 weeks of age), the effects of central administration of insulin combined with resistin on RSNA following a normal diet (ND) and a high fat diet (HFD) (22% fat), since HFD can reportedly attenuate insulin’s actions. RSNA, mean arterial pressure (MAP) and heart rate (HR) responses were monitored and recorded before and for 180 min after intracerebroventricular injection of saline (control) (n=5 HFD and ND), resistin (7 µg; n=4 ND, n=5 HFD), insulin (500 mU; n=6 ND, n=5 HFD) and the combination of both resistin and insulin (n=7 ND, n=5 HFD). The key finding of the present study was that when resistin and insulin were combined there was no increase in RSNA induced in rats fed a normal diet or the high fat diet. This contrasted with the sympatho-excitatory RSNA effects of the hormones when each was administered alone in rats fed theND and the HFD.